Biocomposites: A review of materials and perception. (June 2022) - Manu, T.; Nazmi, Ali Reza; Shahri, Bahareh; Emerson, Nick; Huber, Tim
Abstract: With the increasing global attention on sustainability, biocomposites have been touted as a solution to deal with the issues of unsustainable raw material production, product manufacture and disposal that are common with typical plastic and composite materials. However, after decades of research, the tangible outcomes in terms of impactful raw materials are few and far. It has been observed that though people are more aware of sustainability, this rarely translates into purchasing behaviour favouring biocomposites. In this review, the history of biocomposite development is considered, including their classification, raw materials, commercial aspects and notable products. This review reveals that the presence of a wide range of bio-degradation standards and inconsistent use of 'eco' terms creates confusion amongst consumers and, while many natural materials are valued for their visual aspects, most biocomposites are not. The lack of widespread acceptance for biocomposites could be driven by their lack of desirability and distinguishability. To create favourable perceptual attributes for biocomposites, various mechanisms behind material perception, 'good' experiences and 'natural' perception are reviewed. We propose that biocomposites could be made desirable and distinguishable by modifying the physical characteristics and the perceptual attributes associated with them. Graphical Abstract: ga1 Highlights: Despite stronger environmental awareness, no increase in market demand for biocomposite is noticeable. Disinterest is caused by inferior functional characteristics and poor material perception regarding biocomposites. Perceptual issues of biocomposites could be resolved by improving their desirability and distinguishability. Drivers for better perception are bio-sourcing, compostability, natural aesthetics, uniqueness and material experience. The key drivers for better perception are bio-sourcing, compostability, natural aesthetics, uniqueness and interactive material experience.